Partnerships and Stakeholder Participation in the Management of National Parks: Experiences of the Gonarezhou National Park in Zimbabwe - Walter Musakwa; Trynos Gumbo; Gaynor Paradza; Ephraim Mpofu; Nesisa Analisa Nyathi; Ntlakala B. Selamolela (Land, 2020)
National parks play an important role in maintaining natural ecosystems which are important sources of income and livelihood sustenance. Most national parks in Southern Africa are managed by their states. Before 2007, Gonarezhou National Park was managed by the Zimbabwe Parks Management and Wildlife Authority, which faced challenges in maintaining its biodiversity, community relations and infrastructure. However, in 2017 the Frankfurt Zoological Society and the Zimbabwe Parks Management and Wildlife Authority formed an innovative partnership under the Gonarezhou Conservation Trust (GCT). This study examines the relationship between GCT management, Gonarezhou National Park stakeholders and communities as well as the impact of the relationship on biodiversity and ecosystems. The study also highlights challenges faced and lessons learned in managing Gonarezhou as a protected area. To obtain the information, key informant interviews, Landsat satellite imagery, secondary data from previous studies and government sources were utilized. The results indicate that the concerted efforts of the Gonarezhou Conservation Trust to manage the park are starting to bear fruit in improving biodiversity conservation, ecosystem management and engaging communities. However, challenges such as governance obstacles, problematic stakeholder management, maintaining trust in community relations, ensuring sustainability, managing the adverse impacts of climate change and human-wildlife conflicts must still be navigated to ensure the park’s sustainable management. Notwithstanding challenges, we argue that a partnership arrangement such as the Gonarezhou Conservation Trust is a desirable model that can be applied in national parks in Zimbabwe and Africa for better biodiversity management and tourism.